"I could see the meaning of what I had done": A qualitative study of Chinese healthcare workers' experiences of distress and meaning-making during and after the COVID-19 pandemic - Eric Abraham (Inquiry@Queen's Undergraduate Research Conference Proceedings, 2026)
Healthcare workers in China faced substantial occupational and psychological strain throughout the COVID-19 pandemic, and the end of the zero-COVID policy introduced a distinct period of transition marked by new uncertainties. Whilst existing research has documented their distress during the acute pandemic period, it remains unclear which challenges persisted or emerged for Chinese healthcare workers once restrictions lifted. To develop successful interventions, it is also important to understand how healthcare workers cope with these prolonged challenges and distress. This qualitative study explored how healthcare workers experienced this transition period. Online semi-structured interviews were conducted with 50 healthcare workers across various regions in China. Transcripts were coded by the interviewer to identify initial themes, which were then refined through discussion, and independently recoded by two research assistants to verify them. All participants reported fear of resurgence after reopening and fear of infection was reported by 82%. Despite this, 88% described some form of “silver lining”. Four core themes were identified. (1) Weight of Patient Care- Participants described the emotional toll of patient suffering and death, complicated by non-cooperation from patients and families;(2) Occupational Burden-Heavy workloads, equipment and personnel shortages, and management failures placed strain on participants' work; (3) Living Under Threat- A sustained fear of infection for themselves and others after reopening; (4) Meaning-making- The need to engage in different forms of meaning-making such as professional growth and fostering an increased sense of achievement. The end of the restrictions did not seem to resolve the burden experienced by healthcare workers. Fear, frustration, and uncertainty persisted during the transition, while reopening introduced new concerns. Finding meaning within this experience emerged as a potential means through which healthcare workers can cope. This informs future interventions for healthcare workers by highlighting the value of identifying sources of meaning and growth within a crisis.